Gatewatching Behind the Beating Case of Ratna Sarumpaet in Tribunnews.com and Detik.com - Sundari Sundari; Ummi Salamah (Komunikator, 2019)
The existence of social media fosters a public role in the production of news in online media. Through social media, the public acts as a curator of crucial issues and news sources. This study uses Axel Bruns'sgatewatching theory that emphasizes the role of media audiences in producing news and Gamson's frame theory that explains how journalists tell stories and present constructs of meaning related to news objects. An example of the practice of gatewatching in news production is seen when the mass media created news about the beating of Ratna Sarumpaet on October 2, 2018, which later proved to be hoax information. Detik.com and Tribunnews.com processed information from social media into the news. The framing analysis conducted on the news on both online media shows that the frame was made in line with the perspective of social media users as curators. Consequently, the mass media failed to present news based on facts. Journalists depend on social media users in framing news. The carelessness of the mass media in the practice of gatewatching does not only cause the spread of false news but also violations of journalistic ethics. The mass media might fail to be a guide dog (guide dog) for the reader.